2018
DOI: 10.5935/1984-0063.20180006
|View full text |Cite
|
Sign up to set email alerts
|

A rare differential diagnosis of excessive daytime sleepiness - Artery of Percheron territory infarct

Abstract: Stroke is an example of neurological diseases that can commonly drives Excessive Daytime Sleepiness (EDS). Extensive strokes with brain edema can leave a brain herniation and coma. Other causes of EDS after stroke are strategic lesions at Thalamus and brainstein. A 56-year-old man, right handed, with hypertension and hypercholesterolemia was admitted at Emergency Room due to 5 days onset of EDS, memory impairment, and left-sided weakness. A brain magnetic resonance imaging showed paramedian thalamic hyperinten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…On May 27, 2020, a personal literature review based on a 2015-2020 PubMed search [key items: "artery of Percheron" AND ("case report" OR "case-series")] found 73 papers published in English language (30, 37, and 6 papers included females, males, and both sexes, respectively). Among the 37 studies including only males, 13 reported sleepiness or equivalent terms (i.e., hypersomnolence, drowsiness, or excessive daytime sleepiness) as a delayed complication of an AOP stroke (Table 1; Afana et al, 2019;Aryan et al, 2016;Bailey & Khadjooi, 2016;Goico & Mikesell, 2018;Harisuthan et al, 2018;Ince & Asan, 2018;Kamasak et al, 2015;Khanni et al, 2018;Oliveira et al, 2018;Shah & Ali, 2018;Vasconcellos et al, 2016;Zelante et al, 2015;Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On May 27, 2020, a personal literature review based on a 2015-2020 PubMed search [key items: "artery of Percheron" AND ("case report" OR "case-series")] found 73 papers published in English language (30, 37, and 6 papers included females, males, and both sexes, respectively). Among the 37 studies including only males, 13 reported sleepiness or equivalent terms (i.e., hypersomnolence, drowsiness, or excessive daytime sleepiness) as a delayed complication of an AOP stroke (Table 1; Afana et al, 2019;Aryan et al, 2016;Bailey & Khadjooi, 2016;Goico & Mikesell, 2018;Harisuthan et al, 2018;Ince & Asan, 2018;Kamasak et al, 2015;Khanni et al, 2018;Oliveira et al, 2018;Shah & Ali, 2018;Vasconcellos et al, 2016;Zelante et al, 2015;Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Altered mental status is a classic manifestation of AOP stroke and can range from hypersomnia to coma (Table 1). However, hypersomnia is rarely reported as a first complaint (Cases 1 and 3) since it is usually misdiagnosed as coma or it is lately diagnosed after recovery from coma (Case 2; Bassetti et al, 1996;Hammersley et al, 2017;Hermann et al, 2008;Oliveira et al, 2018). Hypersomnolence (i.e., excessive daytime sleepiness and/or prolonged sleep) in bithalamic stroke is explained by the crucial role of the thalamus in sleep regulation and in maintaining arousal.…”
Section: Discussionmentioning
confidence: 99%
“…The different types of anatomical variations in the PeA distribution are shown in the Figure 2. In PeA occlusion, the classic presentation often consists in vertical gaze palsy, memory impairment and alteration in mental status, with the possibility of confusion and coma 2,6 . Alteration of mental status can range from immediate (40%) to progressive, over hours (60%).…”
mentioning
confidence: 99%
“…Alteration of mental status can range from immediate (40%) to progressive, over hours (60%). It is related with the involvement of the reticular activating system and can be classified into hypersomnia, disorientation, dysarthria, or coma 2,6 . When the involvement is mesencephalic or thalamic, the vertical gaze palsy is seen.…”
mentioning
confidence: 99%
See 1 more Smart Citation